1965
DOI: 10.1037/h0021824
|View full text |Cite
|
Sign up to set email alerts
|

Role of the developing rat testis in differentiation of the neural tissues mediating mating behavior.

Abstract: Male rats castrated at 1, 5, 10, 20, 30, and 90 days of age and females ovariectomized at 90 days of age were compared as adults for female mating behavior when given estradiol and progesterone. The Day-1 and Day-5 castrates displayed more feminine behavior than those castrated after Day 5. When males castrated at similar ages received testosterone as adults, Day 1 and Day-5 castrates displayed fewer intromissions and ejaculations than Ss castrated later. The data support the hypothesis that the action of gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
5
2

Year Published

1967
1967
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(88 citation statements)
references
References 6 publications
(5 reference statements)
4
77
5
2
Order By: Relevance
“…Thus presumably when the ovaries start to secrete estrogens at day 7 after birth [53], AFP no longer plays a significant role. Consistent with a postnatal role of estradiol in feminization of the brain is the observation by Steward and Cygan [93] of an enhanced of female receptivity in neonatally gonadectomized male and female rats treated with estradiol over postnatal days [30][31][32][33][34][35][36][37][38][39][40]. We propose thus that the defeminizing action of estradiol normally occurs prenatally in males and is avoided in fetal females because of the protective actions of AFP.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Thus presumably when the ovaries start to secrete estrogens at day 7 after birth [53], AFP no longer plays a significant role. Consistent with a postnatal role of estradiol in feminization of the brain is the observation by Steward and Cygan [93] of an enhanced of female receptivity in neonatally gonadectomized male and female rats treated with estradiol over postnatal days [30][31][32][33][34][35][36][37][38][39][40]. We propose thus that the defeminizing action of estradiol normally occurs prenatally in males and is avoided in fetal females because of the protective actions of AFP.…”
Section: Discussionmentioning
confidence: 52%
“…Thus female guinea pigs treated with testosterone propionate in utero showed elevated levels of male-typical mounting behavior together with reduced levels of female-typical lordosis behavior in adulthood [75]. Supportive evidence for a role of perinatal testosterone in the development of the male brain came from subsequent studies by Feder and Whalen [31], and Grady et al [40], and many others (reviewed in [10]) showing that removal of testosterone by neonatal castration reduced males' later capacity to show male sexual behaviors while enhancing their ability to show female sexual behaviors. Additional evidence suggested that testosterone secreted by the testes acts perinatally, either directly via androgen receptors or after being aromatized into estradiol and stimulating estradiol receptors ( [58,68]) to masculinize (enhance male-typical sexual responses) and/or defeminize (suppress femaletypical responses) the neural substrate that controls sexual behavior (Fig.…”
Section: Classical Theory Of Brain and Behavioral Sexual Differentiationmentioning
confidence: 78%
See 1 more Smart Citation
“…Serum luteinizing hormone was assayed and Chaikoff by Doctors Robert Eskay and John Porter using a radioion 1-2 weeks immunoassay technique and NIAMD Rat LH-RP-I (Na- (27), in contrast to the testicular feminization syndrome in man (9,28,29), has a defect in testosterone biosynthesis and low testosterone blood levels. Since early castration in the rat has been reported to lead to a variety of secondary changes, including partial androgen insensitivity (30,31), it was necessary to characterize the hormonal status of the Tfmn mice. Therefore, testosterone values were compared in pooled samples of serum from normal male, normal female and Tfmin mice, all between 6 and 8 wk of age (Fig.…”
Section: Estismentioning
confidence: 99%
“…Males castrated at 1 day of age and injected with estrogen and progesterone as adults have been reported by Grady, Phoenix, & Young (1965) to displayas many lordotic responses as similarly injected spayed females. Gerali, Hendricks, Johnson, & Bounds (1968), usingamethod ofscoring receptivity which included quality as weil as frequency of lordosis and soliciting behaviors, found that I-day castrated males' behavior was inferior to that of fern ales spayed within a short time after birth_ Neither study specified the time within the 24-h period after birth at which castration occurred.…”
mentioning
confidence: 99%